The Pandora Papers Opens up Pandora's Box: Integrity in Crisis. (4th March 2023) - Bhuiyan, Shahjahan
Abstract: Integrity lies at the center of state-society interactions, with broad implications for the practice of public administration, governance, and public service delivery. The Pandora Papers leaks are hard examples of integrity violations, shining a light on how public administration operates in practice. The integrity deficits revealed not only threaten people's wellbeing, but also put on display the state's leniency toward rich and powerful people accumulating wealth through corruption, fraud, and tax evasion, among other crimes. In this context, this article attempts to understand whether the Pandora Papers leaks violate of the fundamentals of integrity. Drawing on cases and examples, the findings of the article show that the Pandora Papers illustrate the integrity deficit of statesmen, political leaders, businesspersons, and bureaucrats, the people responsible for ensuring integrity in managing the state and statecraft. The article further elucidates that bad governance affects integrity, both nationally and globally.